Relationship Between Student Perception of School Worthiness and Demographic Factors - Shah, Vishal; Shah, Anand (Frontiers in Education, 2018)
In an era when education is supposed to be means for good jobs and linked to extrinsic values such as fame and money, students are losing interest in school education. The goal of this research is to see if there is any correlation between the students’ views of school worthiness and schoolwork, and demographic variables. Our hypothesis is that several key demographics involving diversity, income, and education will affect how students view school and its importance. Results show that there is no correlation between the demographic variables we analyzed and the student perception of school worthiness.